Corporatization of Salt Farmer: The Dynamic of Social Economic and Ecological Transitions - Baekhaki, Khamid; A. Kinseng, Rilus; Soetarto, Endriatmo (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2018)
ABSTRACTAs an effort to maintain the consumption salt surplus production and to supply industrial needs, Indonesian goverment implement Pengembangan Usaha Garam Rakyat [Devolepment of People Salt Business] by encouraging salt farmers to manage their business using corporate pattern, and bring up a new concept called “corporitization of salt farmer”. They have been requested to use corporate pattern and apply some useful equipments and technology, land integration, formulating contracts, and other corporatization components. The aims of this research is to analyze corporatization model in people salt business by using corporatization concept with some descriptions of the socio-economic transition, and the impact of ecologycal changes. The method used is qualitative and quantitative, starting with survey, focuss group discussion, indepth interview, and observation. The results are (i) the interpretation of corporatization by farmers is diverse, it is different with government conception, (ii) Socio-economic transition indicated by the relation between small-large farmer and salt farmer trader, new incarnation of trader, and the economic farmer revenues, (iii) the dynamics of ecologycal changes caused by intersection with mangrove and housing that will effect of the large ammounts of plastic waste in the future.Keywords: corporate pattern, corporatization, transition of social, economy, and ecologyABSTRAKSebagai upaya mempertahankan surplus garam konsumsi dan mencoba menyediakan garam industri, pemerintah melaksanakan Pengembangan Usaha Garam Rakyat (PUGaR) yang salah satu strateginya mendorong sebagian petambak garam mengelola usaha dengan pola korporasi, hal ini memunculkan konsep “korporatisasi garam rakyat”. Petambak didorong menerapkan peralatan/teknologi tepat guna, integrasi lahan, memperbanyak kontrak dengan perusahaan, dan komponen–komponen korporatisasi lainnya. Tujuan penelitian ini ingin menganalisis pemaknaan korporatisasi dari sudut pandang petambak garam, menganalisis dinamika transisi sosial ekonomi, dan dinamika perubahan ekologi yang ditimbulkan oleh korporatisasi. Metode yang digunakan adalah metode kuntitatif dan kualitatif, dengan teknik pengumpulan data melalui survei, focus group discussion, wawancara dan observasi. Hasil penelitian ini adalah (i) korporatisasi ditanggapi secara beragam oleh petambak garam, yang didasari atas rasionalitas mereka selaku aktor, dan pemakanaan terhadap komponen korporatisasi tidak selalu sama dengan pamaknaan pemerintah, (ii) transisi sosial ekonomi dapat dilihat dari hubungan antara pemilik moda produksi dan pedagang-petambak garam yang mulai bergeser, jelmaan pedagang dalam bentuk baru, dan peningkatan pendapatan petambak garam, (iii) dinamika perubahan ekologi dilihat dari persinggungannya dengan pemukiman dan mangrove belum terlihat secara besar, namun terdapat potensi sampah plastik yang besar di masa mendatang.Kata kunci: pola korporatisasi, pemaknaan korporatisasi, transisi sosial, ekonomi dan ekologi